Bioinspired superamphiphobic surfaces as a tool for polymer-and solvent-independent preparation of drug-loaded spherical particles - Rial-Hermida, Maria Isabel (2014)
Superamphiphobic surfaces were evaluated as a tool to prepare spherical particles from polymers and solvents of very diverse nature, under mild conditions and with 100% drug encapsulation yield. Different from bioinspired superhydrophobic surfaces suitable only for aqueous dispersions, the superamphiphobic platforms allowed the formation of spherical droplets when solvents of any polarity were deposited onto them. Spherical poly(d,l-lactide-co-glycolide) (PLGA) particles were synthesized by placing drops of PLGA/ciprofloxacin suspensions in dioxane on a superamphiphobic surface followed by solvent evaporation. The particles prepared covering a wide range of PLGA/ciprofloxacin weight ratios delivered a 20% dose in the first 24h and then sustained the release of the remaining drug for more than 1month. The particles, both freshly prepared and after being 26days in the release medium, showed efficiency against different types of microorganisms. The developed polymer- and solvent-independent approach could be useful for microencapsulation with very high efficiency of active substances of varied nature into size-tunable particles for a wide range of applications in an affordable and cost-effective manner.